THE SPEECH ACT OF APOLOGY AMONG MACEDONIAN LANGUAGE SPEAKERS (Philological Studies, 2025)
This paper examines the most commonly used strategies and substrategies for apology among the young population in North Macedonia, with the aim to identify similarities and differences in relation to the use of these strategies and substrategies among the adult population. The sample consists of 50 speech acts of apology collected from people aged 21 to 31 years, which represents a kind of corpus. To collect data, a survey with open-ended questions was used, and the analysis relies on a comparison with the results from previous research, qualitative content analysis based on coding, and the interpretative-inductive method.The results show that young people use the same strategies and substrategies as adults. Futhermore, they use more direct strategies, especially the strategy of taking responsibility and its substrategies of explanation and lack of intention. Furthermore, the results confirm that, within this strategy, young speakers do not use the substrategy of ‘the interlocutor is right’ and expressions of embarrassment, at all. The results also show that, in relation to the direct strategy of expressions of apology, young speakers mostly use the substrategies of asking for forgiveness, offering an apology, and expressing regret. The substrategies of foreign words, mitigating factors, and expressions of reconciliation are not observed. Indirect strategies, on the other hand, are used much less frequently than direct ones. Of these, young speakers use the strategy of offering compensation or correcting the error, the most.